LEMAHNYA FUNGSI INTEGRATIF KELUARGA DALAM MEMPERTAHANKAN IKATAN SAUDARA KANDUNG - Siti Puspa Komariah; Puspita Wulandari (JURNAL SOCIUS, 2026)
This study aims to examine how the integrative function of the family, particularly family cohesion and communication patterns, influences the quality of sibling relationships and how individuals construct alternative relationships outside the nuclear family when sibling bonds weaken. In contemporary society, sibling relationships are increasingly perceived as less emotionally significant than peer relationships. This study employs a qualitative descriptive approach through in-depth interviews with two informants who have different family backgrounds, age gaps among siblings, and family dynamics. The findings indicate that low family cohesion, closed communication patterns, unresolved conflicts, and perceived parental favoritism contribute to distant and fragile sibling relationships. Sibling interactions tend to be situational and lack emotional continuity. As a result, individuals seek emotional fulfillment through friendships, which function as alternative sources of support, acceptance, and emotional safety. Friends are perceived as “chosen siblings” who replace the emotional roles traditionally associated with biological siblings. Using Family Systems Theory, this study demonstrates that weakened sibling bonds reflect dysfunction within the broader family system. Disruptions in the integrative function of the family affect the sibling subsystem and encourage emotional cutoff as a coping mechanism. The study highlights that sibling relationship problems should not be understood as individual failures but as outcomes of systemic family dynamics. Strengthening family communication and cohesion is therefore essential to maintaining healthy sibling relationships.